2010
DOI: 10.1098/rspb.2010.0819
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservation advice for despotic populations: habitat heterogeneity favours conflict and reduces productivity in Seychelles magpie robins

Abstract: Individual preferences for good habitat are often thought to have a beneficial stabilizing effect for populations. However, if individuals preferentially compete for better-quality territories, these may become hotspots of conflict. We show that, in an endangered species, this process decreases the productivity of favoured territories to the extent that differences in productivity between territories disappear. Unlike predictions from current demographic theory on site-dependent population regulation (ideal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…In the Seychelles magpie robin (Copsychus sechellarum), it has been demonstrated that interference through territorial disputes increases with increasing density and has the potential to reduce fitness [13]. Similarly, interference effects owing to both territory shrinkage and territorial disputes on reproductive success were crucial for the population dynamics of the Seychelles warbler (Acrocephalus sechellensis) [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Seychelles magpie robin (Copsychus sechellarum), it has been demonstrated that interference through territorial disputes increases with increasing density and has the potential to reduce fitness [13]. Similarly, interference effects owing to both territory shrinkage and territorial disputes on reproductive success were crucial for the population dynamics of the Seychelles warbler (Acrocephalus sechellensis) [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a system regulated by site dependence, improving the quality of breeding sites should allow population size recovery [9,11]. In contrast, if interference mechanisms regulate population size, restoration measures should focus on improving poor habitat patches to reduce heterogeneity in habitat quality and decrease conflict pressure, as recommended for the Seychelles magpie robin [13]. Although increasing the number of sites (nest-boxes) in the best habitat patches might increase the average breeding success of the Mauritius kestrel, this study suggests that such management would have little impact on the population growth rate if not coupled with action at a larger scale to expand high-quality habitat in order to reduce interference competition among juveniles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This conflict reduces the frequency of breeding on territories (figure 1b) [24]. Furthermore, subordinates are more common on the best-quality territories, increasing territorial conflict and reducing breeding success to levels associated with the poorest quality territories (figure 1c) [24,25]. Not surprisingly, territorial conflict has implications for population growth (figure 1d) [24].…”
Section: Biodiversity Science and Conservationmentioning
confidence: 99%